(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The determination of fluid flow characteristics is fundamental in various engineering applications, from hydraulic engineering to aerodynamics. This paper presents an overview of numerical methods used to solve fluid flow problems, with a focus on computational techniques for solving the Navier-Stokes equations, which describe the motion of fluid substances. Key methods discussed include the Finite Difference Method (FDM), the Finite Element Method (FEM), and the Finite Volume Method (FVM). The application of these methods in determining flow characteristics, such as velocity fields and pressure distributions, is demonstrated through practical examples and simulations.